ANALISIS FAKTOR-FAKTOR SENSORY MARKETING PADA MASKAPAI PENERBANGAN (Survei pada Wisatawan Mancanegara yang Pernah Menggunakan The World’s 4 Star Airlines di Bandara Internasional Soekarno-Hatta) - Nugraha, Mochamad Eri; Setiyorini, Heri Puspito Diyah (THE Journal : Tourism and Hospitality Essentials Journal, 2013)
Tourism is an integral part of human life. The sector is growing as it has become a necessity for leisure travelers along with the development of the sociocultures undergoing changes. One of the tourism industries that always increases its growth is the airline industry. As stated in the background above, the author conducted a research on The World's 4 Star Airlines in Asia-Pacific and Southeast Asia. In the study, the author took the title: The Analysis of Sensory Factors in Airline Marketing. The purpose of the study was to obtain results of the confirmatory analysis of the most dominant sensory dimension of marketing The World's 4 Star Airlines at Soekarno-Hatta International Airport. This research was descriptive and verificative, and the method of the research was a descriptive survey and explanatory survey. The samples taken in this study were as many as 100 people from the population of 1.195.596 foreign tourist passengers. The technique of sampling done by the author was a systematic sampling. Data processing was done by using the statistical test through SPSS 20.0 for Windows and AMOS 5. The results showed that the sensory dimension of marketing that was the most dominant was the dimension of sight which was equal to 21:36%. Whereas the most dominant sensory marketing indicator was equal to 10:07%.